Assessment of Risk factors For myocardial Infraction in Sample of Patients Attending in Coronary Care Unit Ward in AL-Zahra hospital-Karbala City - Muna Abdul Kadhum Zeidan; Shatha Ahmed M.A; Makki Hasan kadhum; Diyaa Aldeen al-khateeb (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The objective of the present study is to determine the rate  of myocardial infarction  among sample patients attending in CCU medical ward in AL-Zahra hospital and  to identify factors  associated with the myocardial infarction (age, gender, residence, occupation and educational level ), Family history (hypertensionâ€¦..etc. A case control study conducted in Karbala city / AL-Zahra hospital /medical ward /CCU for cardio pulmonary care unit..  Sampling was  (non probability convenient ) the study  was included  100 cases and 100 controls.. The study was started from 15th July 2015 to the 20th October 2015.  Data was collected by questionnaire to obtain socio- demo graphic information. The  result shows that mean age of the subjects was  49.02Â± 8.3 years, and the 23.5% were Free  profession ; about (24.5%)  of patient with myocardial infarction  were smokers. Analyses of results by (chi-square test ) show that (unemployment, low educational level, Family history for hypertension, overweight, chronic diseases: there is a high significant association between hypertension and myocardial infarction,  smoking and lipid profile )  were significant  factors  associated with myocardial in fraction  . Conclusions  This study showed the rate of myocardial infraction  was 12.5 %  among age group (51-60) year,  factors that were associated with higher rate of myocardial infraction  were unemployment, low educational level, Family history for hypertension, overweight and chronic diseases: there is a high significant association between hypertension and myocardial infarction,  smoking and lipid profile.